Factorial Exploratory Model of Risk Perception - Verstap, Arger (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
The exploration of the dimensions of digital activism was the objective of this work. A non-experimental study was carried out with a non-probabilistic selection of 150 students, considering their affiliation with student organizations. A four-dimensional structure was established; technological habitus, computational self-efficacy, diffusion of innovations and Internet mobilization that explained 48% of the total variance, although the design limited the results to the research scenario, suggesting the extension of the study and the inclusion of variables such as; training, socialization and intention to use the devices and networks.